2009
DOI: 10.5194/acp-9-4023-2009
|View full text |Cite
|
Sign up to set email alerts
|

Oceanic influence on atmospheric mercury at coastal and inland sites: a springtime noreaster in New England

Abstract: Abstract. Continuous measurements of elemental (Hg 0 ) and reactive mercury were conducted at two sites in New Hampshire during a powerful April 2007 noreaster. During the most intense period of the storm, enhancements of ∼30-50 ppqv in Hg 0 were observed at a coastal and a high elevation inland site. This enhancement occurred simultaneously with elevated mixing ratios of three marine tracers, CH 3 I, CH 2 Br 2 and CHBr 3 . These observations suggest a marine source of Hg 0 , possibly outgassing from the ocean… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
17
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 35 publications
6
17
1
Order By: Relevance
“…As there is not enough data to properly discern any statistically significant difference between the sample heights, we have looked only at the data from the 0.9m sample height (2009), so for GEM we can see that a diurnal cycle is present in the 215 data, with a minimum at around 6am and a maximum at around 1pm. This is consistent with observed diurnal cycles in other studies 35,45,65,67,68 and is most likely the result of deposition below a nocturnal boundary layer, leading to an increase at dawn from reemission of mercury to the atmosphere from surfaces, influenced by increased convection and mixing, through temperature and solar radiation, which has the same diurnal pattern 220…”
Section: Measurement Overview 175supporting
confidence: 92%
“…As there is not enough data to properly discern any statistically significant difference between the sample heights, we have looked only at the data from the 0.9m sample height (2009), so for GEM we can see that a diurnal cycle is present in the 215 data, with a minimum at around 6am and a maximum at around 1pm. This is consistent with observed diurnal cycles in other studies 35,45,65,67,68 and is most likely the result of deposition below a nocturnal boundary layer, leading to an increase at dawn from reemission of mercury to the atmosphere from surfaces, influenced by increased convection and mixing, through temperature and solar radiation, which has the same diurnal pattern 220…”
Section: Measurement Overview 175supporting
confidence: 92%
“…3b). These somewhat synchronized changes in Hg 0 mixing ratios at the three sites during the storm supported our hypothesis in Sigler et al (2009b) that strong wind induced enhancement in oceanic emissions of Hg 0 can have a regional influence on ambient levels of Hg 0 that can reach far inland.…”
Section: Windsupporting
confidence: 66%
“…Some studies often found association between high concentrations of mercury and wind direction which points to upwind source regions (e.g., Gabriel et al, 2005;Poissant et al, 2005;Aucott et al, 2009;Sigler et al, 2009a;Baya and van Heyst, 2010), while others detected no correlation (Castillo et al, 2011). In addition, our previous study found a relationship between wind speed and possible oceanic evasion (Sigler et al, 2009b). We hypothesized the impact of the April 2007 Nor'easter on ambient levels of Hg 0 that were reflected in sudden enhancements of 52 ppqv and 26 ppqv over a span of 14 and 12 h at a coastal and inland site, respectively.…”
Section: H Mao Et Al: Speciated Mercury At Marine Coastal and Inlmentioning
confidence: 97%
See 1 more Smart Citation
“…During the day, with increased mixing, the concentration decreases to the daytime minimum. This pattern is contrary to most other studies at rural locations 39,56,57,59,65,67,68 , but has been observed in some studies, including Harwell in 1995/6 29 , and also in Chicago 69 , Seoul 70 and Birmingham AL 59 . This pattern is generally observed at urban locations, 67,71,72 where sources for emission and reemission are more important under any nocturnal boundary layer.…”
contrasting
confidence: 97%